Penyuluhan Perilaku Hidup Bersih dan Sehat pada Siswa SDN 2 Sindanglaut Kab. Cirebon - Suharyani, Ine; Ayunda; Ahadi, Ghany; Fitriani, Vina Nurul; Maryanto, Naida Ajeng; Alifia, Fathiya Putri; Meilani; Tussadiyah, Halimah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Children health is an important aspect of healthy and their growth. The implementation of Clean and Healthy Living Behaviors (Perilaku Hidup Bersih dan Sehat/PHBS) means being able to maintain, improve, and protect one's health from the risk of diseases and environmental conditions that do not support a healthy life. PHBS needs to be applied from an early age, especially in children aged 6-12 years. The implementation of PHBS is not only carried out at home but also in the school. The purpose of this outreach is to provide information to students about PHBS at SDN 2 Sindanglaut. The research method involves lectures, question-and-answer discussions, and practical to wash their hands and brush teeth correctly. This activity was conducted at SDN 2 Sindanglaut Kabupaten Cirebon, West Java, in August 2024. The process of this community service consists of preparation, implementation, and evaluation stages. In the preparation stage, licensing, observation, and program development were carried out; implementation included counseling and demonstrations; and evaluation was conducted through observation and monitoring. The results show that the PHBS counseling successfully improved students' knowledge about proper handwashing and tooth brushing habits. Evaluation with pre-test and post-test conducted orally showed a significant increase in students' knowledge. Support from the school and active participation from the students greatly influenced the success of this activity. The conclusion of this activity is that the PHBS counseling at SDN 2 Sindanglaut successfully increased students' awareness and knowledge about clean and healthy living behaviors. It is recommended that the outreach activities be conducted continuously and involve the active roles of teachers and parents in supporting the implementation of PHBS in the school and home environments to consistently maintain the children's health.